2003
DOI: 10.1038/sj.bjp.0705111
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and necrosis: two distinct events induced by cadmium in cortical neurons in culture

Abstract: 1 Cadmium is an extremely toxic metal commonly found in industrial workplaces, a food contaminant and a major component of cigarette smoke. Cadmium can severely damage several organs, including the brain. In this work, we have studied both the cadmium toxicity on rat cortical neurons in culture and the possible protective eect of serum. 2 Our results indicate that: (1) cadmium is taken up by the neurons in a dose and serum dependent way; (2) cadmium, at concentrations from 1 mM or 10 mM (depending on the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
157
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(170 citation statements)
references
References 70 publications
(79 reference statements)
10
157
0
1
Order By: Relevance
“…5,6) Apoptosis disorders induce a disruption of tissue homeostasis and functions and are associated with many diseases, such as cancer, neurodegenerative disease and toxin-induced disease. 7) Cadmium can induce apoptosis in various tissues and cultured cells, including mouse liver, 8) rat kidney and testis, [9][10][11][12][13] human T cell line (CEM-C12 cells), lymphoma U937 cells, normal hepatocytes, liver L-02 cells, fetal lung fibroblast MRC-5 cells and prostate epithelial cells, [14][15][16][17][18][19] mouse mesangial cells, 20) rat lung epithelial cells, cortical neurons and renal tubular epithelial cells, [21][22][23] and porcine kidney LLC-PK 1 cells. 24) These observations indicate that cell death of the proximal tubule cells in the kidney through apoptotic pathways is one of the key events in cadmium-induced renal toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…5,6) Apoptosis disorders induce a disruption of tissue homeostasis and functions and are associated with many diseases, such as cancer, neurodegenerative disease and toxin-induced disease. 7) Cadmium can induce apoptosis in various tissues and cultured cells, including mouse liver, 8) rat kidney and testis, [9][10][11][12][13] human T cell line (CEM-C12 cells), lymphoma U937 cells, normal hepatocytes, liver L-02 cells, fetal lung fibroblast MRC-5 cells and prostate epithelial cells, [14][15][16][17][18][19] mouse mesangial cells, 20) rat lung epithelial cells, cortical neurons and renal tubular epithelial cells, [21][22][23] and porcine kidney LLC-PK 1 cells. 24) These observations indicate that cell death of the proximal tubule cells in the kidney through apoptotic pathways is one of the key events in cadmium-induced renal toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…We were interested in showing this process in neurons as we have previously observed that changes in intracellular Zn 2+ following its liberation from intracellular sites (Aizenman et al, 2000) can result in the activation of MAPK-dependent cell death pathways (Du et al, 2002;McLaughlin et al, 2001;Pal et al, 2003). These molecular pathways may therefore be also activated, albeit indirectly, by Cd 2+ , a highly neurotoxic metal (López et al, 2003). However, since there are no available chelators that can effectively distinguish between Cd 2+ and Zn 2+ , we are unable to determine at this point the relative contribution of Zn 2+ liberation to Cd 2+ neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR has been widely recognized as a central controller of cell proliferation, growth and survival (Bjornsti and Houghton, 2004). Cadmium-induced inhibition of cell proliferation and cell viability has been reported (Lopez et al, 2003;Kim et al, 2005). Akt positively regulates mTOR, leading to increased phosphorylation of ribosomal p70 S6 kinase (S6K1) and eukaryotic initiation factor 4E binding protein 1 (4E-BP1), the downstream effector molecules of mTOR (Bjornsti and Houghton, 2004).…”
Section: Discussionmentioning
confidence: 99%